2020
DOI: 10.3390/ma13030533
|View full text |Cite
|
Sign up to set email alerts
|

Axial Compressive Behavior of Geopolymer Recycled Lump Concrete

Abstract: To reduce the environmental pollution from cement production and the damage to natural resources from aggregate mining in the concrete industry, a relatively new concrete, termed geopolymer recycled lump concrete (GRLC), which uses geopolymer as the binding material to replace traditional cement and uses large demolished concrete lumps (DCLs) to partly replace concrete, is prepared in this study. Cubic and cylindrical GRLC specimens containing fresh geopolymer concrete and DCLs were tested under axial compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It is worth noticing that identical observations were also reported in other experimental investigations, such as. 77,78 Moreover, it was found that the measured elastic modulus values of GPC were lower than those calculated using the Australian Standard AS3600 (2005), and the American Concrete Institute (ACI) Committee 363 (1992). 11 On the other hand, in Nath and Sarker, 15 the authors stated that the modulus of elastic of GPC was relatively less than that of OPC concrete of similar compressive strength (from about 25% to 31.1% depending on the testing age).…”
Section: Resultsmentioning
confidence: 93%
“…It is worth noticing that identical observations were also reported in other experimental investigations, such as. 77,78 Moreover, it was found that the measured elastic modulus values of GPC were lower than those calculated using the Australian Standard AS3600 (2005), and the American Concrete Institute (ACI) Committee 363 (1992). 11 On the other hand, in Nath and Sarker, 15 the authors stated that the modulus of elastic of GPC was relatively less than that of OPC concrete of similar compressive strength (from about 25% to 31.1% depending on the testing age).…”
Section: Resultsmentioning
confidence: 93%
“…Generally, the goal of such actions, which have been implemented for many years, is: to reduce the environmental pollution from cement production and the damage to natural resources from aggregate mining in the concrete industry [8], and to limit the use of natural raw materials needed for clinker burning (this process requires approximately 1.7 tons of raw materials, mainly limestone, per ton of clinker produced [9]; 6.97 bn tons per year), as a result of which it would be possible to reduce the amount of energy that is needed to produce cement and reduce the greenhouse gases (GHG) generated in these processes; mainly CO 2 . Therefore, the assumption of the production of low-emission cements would be possible with a reduction of the clinker/cement ratio to 0.7, which is supposed to happen in 2050.…”
Section: Figure 2 World Production Of Cement and Clinker By Country I...mentioning
confidence: 99%
“…It is a new type of green building material. Compared with the compressive behavior of geopolymer recycled concrete and cement recycled concrete, Zhang found [26] that geopolymer recycled concrete possesses higher compressive strength than cement recycled concrete under the same experimental conditions, due to the strengthening effect of fresh geopolymer binding material. Moreover, a modified method for predicting the compressive strength of geopolymer recycled concrete cubic and cylindrical specimens was proposed.…”
Section: Introductionmentioning
confidence: 98%